コウクウキ シヨウ ノ ゲンジョウ ト テンボウ - 村越, 望; ムラコシ, ノゾミ; 佐野, 雅史; サノ, マサシ; Murakoshi, Nozomi; Sano, Masashi (1985)
P(論文) 南極地域観測が始まった1956年以来, 小型飛行機が必要に応じて使用されてきた。第12次観測隊までは夏期間だけの使用であり, 輸送・建設期間が短いこともあって飛行時間は毎回55時間を超えることはなかった。その後, 2年越冬1年持ち帰りという周期をとり, 安全のために2機を越冬させている。最近では年間の飛行時間は350時間を超えている。操縦士2人と整備士1人がセスナ185型1機とピラタスPC-6型1機を運航している。飛行機は海氷上で離着陸をし, 駐機もしているので, 夏のパドルの発生や強風に対する係留, 海氷の流失など面倒な問題が多い。安全を確保するために, 良い天気を選ぶこと, 飛行計画に余裕をもたせること, 整備上や飛行状態の過程における確認に十分気をつけている。 A small fixed wing aircraft was used in the summer seasons from the First Japanese Antarctic Research Expedition (JARE-1,1956-57) to JARE-12 (1970-71) at Syowa Station, Antarctica. However, flight hours were less than 55 hours in each summer season because of the limited operation period of relief ships in the vicinity of Syowa Station. In recent years, one Cessna 185 and one Pilatus PC-6 were operated throughout the year at Syowa Station by two pilots and one mechanic, stationing the aircraft for two years at Syowa and repatriating one year. The recent total yearly flight hours are over 350 hours. Since the aircrafts are operated from a sea-ice runway, several problems are experienced such as the deterioration of the runway surface during midsummer, mooring of aircraft, and sea ice breaking. To ensure the safe operation, various precautions are taken on flight plan, maintenance of aircraft, weather observations, and other matters. departmental bulletin paper